2020
DOI: 10.1108/bfj-10-2019-0762
|View full text |Cite
|
Sign up to set email alerts
|

Consumer preferences for three dimensions of country of origin of a processed food product

Abstract: PurposeThe production process of processed food products may involve several countries. This multi-dimensionality of the country of origin (COO) may affect consumer preferences for the products. We apply Case 2 best–worst scaling to measure Japanese consumers’ preferences for three dimensions of the COO of a vegetable juice product.Design/methodology/approachThe three dimensions of the COO include these: the country where the raw materials of the product were grown (the country of growing), the country where t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 37 publications
0
20
0
Order By: Relevance
“…A majority of participants were unaware of the country of origin of the rice they purchase; there is some evidence that in non-rice eating countries, country of origin is not an important attribute in consumer decision-making [15,107]. In other product categories, geographic origin may be a factor in food preferences if the origin is somehow associated with quality [108,109]. Nonetheless, these responses suggest some degree of awareness among UK consumers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A majority of participants were unaware of the country of origin of the rice they purchase; there is some evidence that in non-rice eating countries, country of origin is not an important attribute in consumer decision-making [15,107]. In other product categories, geographic origin may be a factor in food preferences if the origin is somehow associated with quality [108,109]. Nonetheless, these responses suggest some degree of awareness among UK consumers.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies have found that consumers' preferences and willingness to pay for biodiversity or reduced CO 2 are relatively lower when they are offered as a choice among other ethical attributes [109,122,123]. Prior research provides evidence that consumers value biodiversity if it is local [122,124], and that consumers may pay for CO 2 reductions if the actions are local [123].…”
Section: Discussionmentioning
confidence: 99%
“…Much of the research indicates that intrinsic attributes such as color, size, flavor etc. are important attributes for consumers’ purchasing decisions of agricultural products (Moor et al , 2014; Wang et al , 2018; Aizaki and Sato, 2020; He et al , 2021; Liu et al , 2020). Research also indicates that extrinsic attributes, like origin and brand, are crucial for consumers to make purchase decisions of agricultural products (Novotorova, 2008; Migliore et al , 2015; Yin et al , 2019).…”
Section: Literature Review and Analysis Frameworkmentioning
confidence: 99%
“…Furthermore, processed food products are similar to industrial products because the processing stage of processed food is similar to the manufacturing stage of industrial products (Aizaki and Sato, 2020). Compared to unprocessed food, processed food attributes are more comprehensive and complex because processed food production involves more players along the supply chain.…”
Section: Literature Review and Analysis Frameworkmentioning
confidence: 99%
See 1 more Smart Citation